Trigo-fying

Geometry Level 3

If A = cos π 5 cos 2 π 5 A=\cos {\frac{\pi}{5}}\cos {\frac{2 \pi}{5}} and B = cos π 5 cos 2 π 5 B=\cos {\frac{\pi}{5}}-\cos {\frac{2 \pi}{5}} . Then 1 A + 1 B = ? \dfrac{1}{A}+\dfrac{1}{B}=\boxed{?}


The answer is 6.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Noel Lo
Jul 17, 2017

A = c o s π 5 c o s 2 π 5 = 2 s i n π 5 c o s π 5 c o s 2 π 5 2 s i n π 5 = s i n 2 π 5 c o s 2 π 5 2 s i n π 5 = 2 s i n 2 π 5 c o s 2 π 5 4 s i n π 5 = s i n 4 π 5 4 s i n π 5 = s i n π 5 4 s i n π 5 = 1 4 A=cos {\frac{\pi}{5}}cos {\frac{2 \pi}{5}}=\frac{2sin {\frac{\pi}{5}}cos {\frac{\pi}{5}}cos {\frac{2 \pi}{5}}}{2 sin {\frac{\pi}{5}}}= \frac{sin {\frac{2 \pi}{5}} cos {\frac{2 \pi}{5}}}{2 sin {\frac{\pi}{5}}} =\frac{2sin {\frac{2 \pi}{5}} cos {\frac{2 \pi}{5}}}{4 sin {\frac{\pi}{5}}}=\frac{sin {\frac{4 \pi}{5}}}{4sin {\frac{\pi}{5}}}=\frac{sin {\frac{\pi}{5}}}{4sin {\frac{\pi}{5}}}=\frac{1}{4}

B = c o s π 5 c o s 2 π 5 = 2 s i n 3 π 10 s i n π 10 = 2 c o s π 5 c o s 2 π 5 = 2 A = 2 × 1 4 = 1 2 B=cos {\frac{\pi}{5}}-cos {\frac{2 \pi}{5}}=2 sin {\frac{3 \pi}{10}} sin {\frac{\pi}{10}}=2 cos {\frac{\pi}{5}}cos {\frac{2 \pi}{5}}=2A=2 \times\frac{1}{4}=\frac{1}{2}

Therefore,

1 A + 1 B = 4 + 2 = 6 \frac{1}{A}+\frac{1}{B}=4+2=\boxed{6}

Chew-Seong Cheong
Jul 28, 2017

We note that k = 0 n 1 cos 2 k + 1 2 n + 1 π = 1 2 \displaystyle \sum_{k=0}^{n-1} \cos \frac {2k+1}{2n+1} \pi = \dfrac 12 (see proof ). Then we have,

cos π 5 + cos 3 π 5 = 1 2 Note that cos ( π x ) = cos x cos π 5 cos 2 π 5 = 1 2 B = 1 2 \begin{aligned} \cos \frac \pi 5 {\color{#3D99F6}+ \cos \frac {3 \pi}5} & = \frac 12 & \small \color{#3D99F6} \text{Note that }\cos (\pi - x) = - \cos x \\ \cos \frac \pi 5 {\color{#3D99F6}- \cos \frac {2 \pi}5} & = \frac 12 \\ \implies B & = \frac 12 \end{aligned}

A = cos π 5 cos 2 π 5 = 1 2 ( cos ( 2 π 5 π 5 ) + cos ( 2 π 5 + π 5 ) ) = 1 2 ( cos π 5 + cos 3 π 5 ) = 1 2 ( 1 2 ) = 1 4 \begin{aligned} A & = \cos \frac \pi 5 \cos \frac {2 \pi}5 \\ & = \frac 12 \left(\cos \left(\frac {2 \pi}5 - \frac \pi 5 \right) + \cos \left(\frac {2 \pi}5 + \frac \pi 5 \right) \right) \\ & = \frac 12 \left(\cos \frac \pi 5 + \cos \frac {3\pi}5 \right) \\ & = \frac 12 \left(\frac 12 \right) \\ & = \frac 14 \end{aligned}

1 A + 1 B = 4 + 2 = 6 \implies \dfrac 1A + \dfrac 1B = 4 + 2 = \boxed{6}

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...